Roses are pink, your feet really stink - De Groat, Diane (New York : Morrow Junior Books, 1996)
On Valentine's Day, Gilbert brings a tin of homemade cookies and his original nice or nasty poems to school.
6 13 18 21 29 30 38 39
Keywords: Valentine's Day -- Fiction; Valentines -- Fiction